Influence of Rotation Speed of Mtwo Files on Root Canal Instrumentation Time with Different Canal Curvatures - Carlesi, Teocrito; Plotino, Gianluca; Colangeli , Mauro; Pappalardo , Alfio; Malagnino, Vito Antonio (Iranian Endodontic Journal, 2021)
Introduction: The aim of this study was to analyze the effect of rotation speed on the instrumentation time of root canals with different curvatures using Mtwo NiTi rotary instruments. Methods and Materials: Forty root canals were selected and divided into 2 groups, according to the angle of curvature (group A>30°, group B<30°). Both groups were divided into 2 subgroups (n=10), according to the rotational speed used for root canal instrumentation (150 rpm: group A1 and B1; 250 rpm: group A2 and B2). The total instrumentation time and the total number of instrumentation cycles (NCI) required to complete root canal preparation were registered for each canal. The mean and standard deviation were then calculated. Data were then statistically analyzed using two-way ANOVA and interaction effect P-values (P<0.05). Results: During root canal instrumentation, there were no file fractures. Total instrumentation time of the low speed groups A1 (150 rpm) and B1 (150 rpm) were significantly higher (P<0.05) than that of the high speed groups, A2 (250 rpm) and B2 (250 rpm); however, there was no statistically significant difference in terms of NCI between the different groups (P>0.05). Statistical difference was not found between the different angles of curvature, group A1 vs B1 and A2 vs B2 in terms of total instrumentation time (P>0.05) and NCI (P>0.05). Conclusions: This ex-vivo study showed that canal preparation with Mtwo rotary files could be completed safely with an increase of the instrumentation time at low rotational speed independently of the root canal curvature.